Nutrient Analysis of Grass Species Consumed by Greater One-Horned Rhinoceros (Rhinoceros Unicornis) in Chitwan National Park, Nepal - Thakur, S.; Upreti, C.R.; Jha, K. (International Journal of Applied Sciences and Biotechnology, 2014)
The Greater One-horned Rhinoceros (Rhinoceros unicornis) is found almost exclusively in Nepal and North-Eastern India. There have beenonly a few studies made on the food and the nutrient compositions of fodder species preferred by The Greater One- horned Rhinoceros. Thepresent study identifies the nutrient content of the fodder species consumed by One-horned rhinoceros which would be helpful to develop proper strategies for rhinoceros food management. For this altogether 8 grass species which were most preferred by rhinoceros were collected from Chitwan National Park. Systematic sampling was applied for sample collection and collected samples were taken to the Animal Nutrition Laboratory, Khumaltar for nutrient analysis. Among all the collected species the highest OM% was seen in Faank (93.98 ± 0.88) while Ash% and CP% was found to be highest in Eragrastic Tenella (13.67 ± 2.92) and Phragmatic karka (11.94 ± 2.26) respectively. Lowest NDF% was again seen in Eragrastic tenella (76.76 ± 2.93) and lowest ADF% and ADL% were found in Mala dubo with mean values (43.50 ± 6.86) and (6.41 ± 2.16) respectively showing high digestibility of these grasses. There were only slight variation in the EE% of the grass species withhighest mean value of (3.702 ± 1.73) of Imperata cylindrical to lowest mean value of (1.722 ± 0.11) of Eragrastic tenella. Highest energy was found in Faank (4181.90 ±1.10) and Calcium content was seen highest in Cynodon dactylon (1.30 ± 0.83). DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11119 Int J Appl Sci Biotechnol, Vol. 2(4): 402-408